PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO - Sarah Septiani; Bono Prambudi (Journal of Management Small and Medium Enterprises (SMEs), 2021)
The purpose of this study is to analyze the effect of product quality and price on purchasing decisions for Oppo smartphones, empirical studies; Pesona Square Mall Depok, Depok Town Square, Margo City Depok, ITC Depok and Depok Mall. The number of respondents who were sampled was 100 people, with the sample criteria; (i). Oppo smartphone users, and (ii). ever been to Pesona Square Depok Mall, Depok Town Square, Margo City Depok, ITC Depok or Depok Mall. Sampling using nonprobability sampling technique. The method uses purposive sampling, namely the sampling technique with certain considerations, so the samples selected are people who meet the criteria mentioned above. By using the Roa Purba formula, the methods used in it include; Analysis of the validity, reliability, classical assumption test, multiple linear regression analysis, F test, t test and coefficient of determination (SPSS Version 22). The result is that Product Quality (X1) does not have a significant effect on Purchase Decisions (Y), meaning that the quality of Oppo smartphone products is not a determining factor in purchasing decisions. While the price variable (X2) has a positive and significant effect on Purchase Decision (Y), meaning that the higher the price of the Oppo smartphone, the more it will increase the purchasing decision. Keywords : Product Quality, Price, Purchase Decision